Effect of detritus decomposition time on Aedes aegypti oviposition site selection and immature developmental success - Arnaldo, Candela M. (2022)
The abundance of the mosquito Aedes aegypti in larval habitats (containers with water) depends on the selection of oviposition sites by the females and on the subsequent survival of the immatures. Both can be affected by factors such as the decomposition time of the detritus, which determines the number of microorganisms (larval food) in the habitat. Females would be expected to select sites where larvae have the best performance to maximize their fitness. The aim of this work is to study the relationship between the selection of oviposition sites in response to detritus age, and the survival of immatures in these sites. To achieve this, an oviposition study and an immature development study were performed. In both studies, three treatments with different decomposition times of detritus in water (3, 15, and 45 days) were used.